PERUBAHAN IKLIM DAN POTENSI ENERGI SURYA DI WILAYAH MONSUN - Erlina Natasya Kurniasari; Gusti Rusmayadi; Totok Wianto; Idiannor Mahyudin (Universitas Lambung Mangkurat, 2023)
Climate change results from global warming, caused by increasing greenhouse gases in the atmosphere, especially CO2 (carbon dioxide). This increase cannot be separated from the excessive use of fossil fuels such as oil and coal in the energy sector. In addition, mining can cause environmental damage, such as reduced air and water quality, and exacerbate future climate change. Renewable energy can be a solution to meet electrical energy needs by minimizing the impact it causes. Solar energy is one environmentally friendly source of renewable energy that will never run out. An analysis of climate change and the potential for solar energy has been carried out in this study. Data processing results for the last 30 years (1992-2021) show that climate change has occurred in the monsoon region. This is marked by a significant increase in the annual average temperature trend and an increase in extreme minimum temperature events until 2021. Based on the results of the projection of solar energy potential using the RCP4.5 scenario for the monsoon region until 2050 of 4.56-5.03 kWh/m2.day with homogeneous data distribution.